THE CORRELATION BETWEEN STUDENT’S MATHEMATIZATION AND MATHEMATICAL DISPOSITION IN IMPLEMENTING GENERATIVE LEARNING - Pratomo, Saifurrahman Iman; Firmansyah, Eka (International Journal of Education, 2017)
This paper reports the result of an experiment with a pretest-posttest control group design, which aims to find out the role of generative learning model and student’s basic mathematical knowledge (BMK) in the improvements of students’ mathematization and the correlation between students’ mathematization and mathematical disposition. The subjects of the study included 73 eight grade students of a junior high school. The instrument of this study was a set of mathematical tests adopted from the Indonesian National Examination (UN). The data were analyzed using t-test and non-parametric Mann-Whitney U test. This study finds that the generative learning model had effects on students’ mathematization and basic mathematical knowledge (BMK).